2014
DOI: 10.1002/ange.201403638
|View full text |Cite
|
Sign up to set email alerts
|

Antifreezes Act as Catalysts for Methane Hydrate Formation from Ice

Abstract: Contrary to the thermodynamic inhibiting effect of methanol on methane hydrate formation from aqueous phases, hydrate forms quickly at high yield by exposing frozen watermethanol mixtures with methanol concentrations ranging from 0.6-10 wt % to methane gas at pressures from 125 bars at 253 K. Formation rates are some two orders of magnitude greater than those obtained for samples without methanol and conversion of ice is essentially complete. Ammonia has a similar catalytic effect when used in concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…19 Thirdly, both Comment 2 authors contributed to one of the first articles that suggested a catalytic effect of NH 3 on the formation of clathrate hydrates. 13 Peak area ratios reported in our article 1 on CH 4 hydrates at 0% NH 3 are consistent with those of sI CH 4 hydrates. 20 Given the suggested catalytic effect of NH 3 on hydrate formation, using the same duration to form the hydrates in its presence would be anticipated to also promote the conversion into sI if a metastable sII had formed first.…”
Section: On Lack Of Evidence For Incorporation Of Nh3 In Ch4 Hydrates...supporting
confidence: 83%
See 2 more Smart Citations
“…19 Thirdly, both Comment 2 authors contributed to one of the first articles that suggested a catalytic effect of NH 3 on the formation of clathrate hydrates. 13 Peak area ratios reported in our article 1 on CH 4 hydrates at 0% NH 3 are consistent with those of sI CH 4 hydrates. 20 Given the suggested catalytic effect of NH 3 on hydrate formation, using the same duration to form the hydrates in its presence would be anticipated to also promote the conversion into sI if a metastable sII had formed first.…”
Section: On Lack Of Evidence For Incorporation Of Nh3 In Ch4 Hydrates...supporting
confidence: 83%
“…The Comment 2 points to Raman (p. 1, last paragraph starting on left column) and X-ray diffraction (XRD, p. 1, right column, first full paragraph) results presented in a study of the ternary H 2 O–NH 3 –CH 4 and H 2 O–CH 3 OH–CH 4 systems 13 to justify that some variability in peak area ratio, hence cage occupancy (from Raman) and in lattice parameter (from XRD) constitutes evidence for NH 3 incorporation in clathrate hydrates in those systems. However, the cited study 13 shows, in their Table 1, a peak area ratio of large cages over small cages somewhat higher in the presence of 1.4% NH 3 than in the pure CH 4 case (albeit at lower pressure), and then a much lower peak area ratio in the presence of 2.7% NH 3 than in both cases. No clear trend seems to emerge from these results.…”
Section: On Lack Of Evidence For Incorporation Of Nh3 In Ch4 Hydrates...mentioning
confidence: 99%
See 1 more Smart Citation
“…There are two major classes of inhibitors used for controlling hydrate formation and growth. Thermodynamic inhibitors, such as methanol, shift the equilibrium for hydrate formation (4), but due to their high cost, safety concerns, and potential to catalyze hydrate formation (5), there has been a move toward the application of kinetic hydrate inhibitors (KHIs). Unlike thermodynamic inhibitors, KHIs can delay hydrate nucleation and/or interfere with the crystal growth (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…That means the guest molecules may affect the formation kinetics of gas hydrates in the presence of promoters such as leucines. It is possible that gas hydrate crystal morphologies are affected by the gas composition,8 or that the same molecule can work as a promoter or an inhibitor depending on the particular conditions of the experiment,14 although a detailed mechanistic study is outside the scope of this first report.…”
mentioning
confidence: 99%